TINGKAT KOMPETISI JATI PLUS PERHUTANI PADA UMUR 6 SAMPAI 11 TAHUN DI KPH SARADAN - , FARID ZIKRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Jati plus Perhutani (JPP) produced from clonal Seed orchard was developed to improve the productivity of teak. This research is needed to provide the information of JPP growth to determine the competition level of JPP from age 6 to 11 years at KPH Saradan. Competition zone was determined by observation of JPP stands which have good productivity and accessible criteria. The sample unit is dominant tree which surrounded by 8 competitor trees. Thirty tree samples were taken. Parameters are the average value of canopy size at 4 cardinal directions and the widest canopy height. Competition Zone was used to determine tree competitor for the subject tree. Hegyi method was used to determine the competition index for each tree sample. Parameters for determining the value of the competition index were the distance between the sample trees with competitor trees, the diameter, and the height of trees. The results of this research are: 1) JPP stands competition zone at the age of 6 to 11 years in a row is worth 27.02o